Development Factors of Non-Governmental Organizations as Institutions of Civil Society - Ikramjon Batirovich Masharipov, (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article provides a scientific theoretical analysis of the need to support non-governmental non-profit organizations and other institutions of civil society, the factors of creating convenience, guaranteeing their freedom, and strengthening social partnership between state bodies, as well as the basics of improving the legal framework regulating this field, as well as the essence of the development of non-governmental non-profit organizations, political parties, which are considered the most important institutions of civil society in Uzbekistan in recent years.